Additive for producing tablet active carbon from long flame coal and its application
Patent Information
- Application Number
- CN202611469059.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0010]为解决以长焰煤为单一原料制备压块活性炭时,堆积密度无法达到550 g/L以上、且对强粘结性煤/煤沥青/强碱性化合物过度依赖的技术问题,本发明公开了一种长焰煤生产压片活性炭的添加剂
[0037]一、堆积密度高:本发明以长焰煤为单一原料,产品堆积密度可稳定达到550 g/L以上,与依赖昂贵强粘结性煤的配煤工艺处于同一最高水平,但原料成本大幅降低,供应链显著简化。
Smart Images

Figure SMS_31 
Figure SMS_32 
Figure SMS_34
Abstract
Description
Technical Field
[0001] This invention belongs to the field of activated carbon preparation technology, specifically relating to an additive for producing flaked activated carbon from long-flame coal, and a method for preparing high-bulk-density, high-iodine-value briquetted activated carbon using the additive. Background Technology
[0002] Granulated activated carbon, made from pulverized coal through high-pressure molding, carbonization, and activation, is widely used in fixed-bed adsorption devices for water treatment, gas purification, and solvent recovery. Bulk density (also known as bulk specific gravity) is one of the core indicators for evaluating the economic viability of activated carbon products: with a fixed adsorption equipment volume, a higher bulk density means a larger mass of activated carbon packed per unit volume, resulting in stronger adsorption capacity and higher market value. Therefore, maximizing bulk density while ensuring iodine adsorption value has long been a core technological goal pursued in this field.
[0003] However, there is an inherent and irreconcilable contradiction between the bulk density and iodine adsorption value of briquetted activated carbon. A higher iodine value means a more developed microporous structure of activated carbon, but the rapid development of micropores inevitably leads to a looser carbon skeleton, resulting in a decrease in bulk density. For high-performance products with iodine values ≥1000 mg / g, the bulk density is typically only 340~380 g / L when using conventional single-flame coal processes, which is insufficient to meet market demands for high packing density.
[0004] To balance high iodine value and high bulk density, the industry has developed coal blending and additive schemes. Among them, patent publication number CN106044766B discloses a method for preparing activated carbon using a blend of non-caking coal (80-90 wt%) and strongly caking coal (5-15 wt%), with the addition of coal tar pitch (3-7 wt%) and a strong alkaline compound (0.2-1 wt%). The technical concept is as follows: utilizing the high apparent density (not less than 1.30 g / cm³) of non-caking coal to provide the basic skeleton density; utilizing the high reactivity and caking properties of strongly caking coal (caking index 70-90) to promote skeleton formation during carbonization; utilizing the tar pitch to provide initial strength during the briquetting stage and form a binding filler after carbonization; and utilizing the strong alkaline compound (…). This method utilizes an internal pore-forming reaction to enhance adsorption. Through the complementary properties of the aforementioned multi-component raw materials, a bulk density exceeding 550 g / L can be achieved even with an iodine value >1050 mg / g. However, this technical route suffers from the following significant drawbacks:
[0005] First, it is highly dependent on raw materials and has high costs: This method requires the use of highly caking coal (caking index 70-90, such as gas-rich coal and coking coal). Such coals are scarce, unevenly distributed, and significantly more expensive than ordinary thermal coal, resulting in high production costs. At the same time, coal tar pitch and strongly alkaline compounds also increase the complexity of raw material procurement and management.
[0006] Second, environmental protection and corrosion issues are prominent: Coal tar pitch produces a large amount of toxic fumes such as polycyclic aromatic hydrocarbons during carbonization, which are difficult to treat and have high environmental protection costs; Strong alkaline compounds (such as KOH and NaOH) severely corrode production equipment, which not only increases equipment maintenance costs, but also introduces alkali metal impurities such as potassium and sodium into the product, reducing the quality of activated carbon.
[0007] Third, the technology suffers from poor applicability to various coal types: it fundamentally relies on a blend of non-caking and highly caking coals. For long-flame coal, which has the richest reserves and lowest mining costs in my country, its high volatile matter content, near-zero caking index, and disordered carbon microcrystalline structure make it impossible to achieve high bulk density through this blending method. If a small amount of pitch and strong alkali are forcibly added to long-flame coal without blending, the lack of skeletal support from highly caking coal prevents effective bonding and shrinkage synergy between coal particles during carbonization, resulting in substandard product bulk density and strength.
[0008] Long-flame coal is one of the most abundant and lowest-cost coal types in my country. If long-flame coal could be used as a single coal type to produce briquetted activated carbon with a bulk density ≥550 g / L and an iodine value ≥1000 mg / g without relying on strongly caking coal, bitumen, or strong alkalis, it would greatly expand raw material sources, reduce production costs, and completely solve environmental problems. However, due to the disordered microcrystalline structure and lack of interparticle binding force in long-flame coal, there is currently no technical solution in the industry that can increase the bulk density of activated carbon made solely from long-flame coal to above 550 g / L without relying on blending, bitumen, or strong alkalis.
[0009] Therefore, developing a new additive and supporting process specifically for long-flame coal, enabling it to produce high-bulk-density, high-iodine-value briquetted activated carbon as a single coal type, has significant practical implications and an urgent need for industrialization. Summary of the Invention
[0010] To address the technical problems of insufficient bulk density (above 550 g / L) and excessive reliance on strongly caking coal / coal tar pitch / strong alkaline compounds when preparing briquetted activated carbon using long-flame coal as the sole raw material, this invention discloses an additive for producing briquetted activated carbon from long-flame coal.
[0011] This invention also discloses the application of an additive in the production of flamed activated carbon from long-flame coal. The entire process is environmentally friendly and low-cost, and the bulk density of the resulting flamed activated carbon is increased to more than 550 g / L, while maintaining an iodine value of ≥1000 mg / g.
[0012] To achieve the above objectives, the technical solution adopted by the present invention is as follows: an additive for producing flamed activated carbon from long-flame coal, which is composed of the following components by mass percentage: 5%~10% phosphorus compound, 10%~20% boron compound, 5%~15% nitrogen-containing organic compound, and 55%~80% carbonaceous filler.
[0013] The phosphorus compound is one or any combination of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate, with ammonium dihydrogen phosphate being preferred.
[0014] Phosphorus compounds release thermal decomposition during carbonization and This process moderately creates pores in the carbon skeleton; more importantly, phosphorus atoms embed into the interlayer spaces of carbon microcrystals at high temperatures, inducing the originally disordered, randomly layered graphite microcrystals of long-flame coal to undergo ordered rearrangement through PC chemical bonds, reducing the interlayer spacing of carbon layers and significantly increasing the intrinsic density of the carbon skeleton at the nanoscale. This is the chemical basis for achieving high packing density. XRD characterization data (Table 2) confirms that after the addition of phosphorus compounds, the 002 diffraction peak of activated carbon... Move to Interlayer spacing The carbon skeleton's order and density were significantly improved, decreasing from 0.367 nm to 0.354 nm and increasing from 1.12 nm to 1.38 nm.
[0015] The boron compound is one or any combination of boric acid, ammonium borate, and borax, with boric acid being preferred.
[0016] Mechanism of action: In the temperature range of 450~500℃, boron compounds undergo dehydration to form , With the abundant oxygen-containing functional groups on the surface of the long-flame coal skeleton ( , A chemical reaction occurs, forming Covalent cross-linked network. This network, like molecular-level welding points, firmly binds the originally loose carbon particles, greatly reducing the packing gaps between particles. At the same time, it cross-links the phosphorus-induced ordered microcrystals into a robust overall framework, significantly improving the product's strength and packing density.
[0017] The nitrogen-containing organic compound is one or any combination of melamine, urea, and caprolactam, with melamine being preferred.
[0018] Mechanism of action: Nitrogen-containing organic compounds are slowly released during pyrolysis. The carbon skeleton is uniformly activated in a secondary gas phase using gases, forming abundant microporous channels to compensate for the micropore volume that may be reduced due to the extreme densification of the carbon skeleton. Simultaneously, nitrogen atoms are in-situ doped into the carbon lattice at high temperatures, forming strong adsorption active sites such as pyridine nitrogen and pyrrole nitrogen, significantly enhancing the surface polarity and adsorption capacity of the activated carbon. XPS characterization data (Table 3) confirms that nitrogen was successfully doped into the carbon skeleton, with pyridine nitrogen (40.1%) and pyrrole nitrogen (33.7%) accounting for a total of 73.8%, providing direct chemical evidence that the iodine value can be consistently maintained at ≥1000 mg / g.
[0019] The carbonaceous filler is one or any combination of nano-carbon black, carbon nanotubes, pyrolytic carbon black, and coal-based ultrafine powder, preferably pyrolytic carbon black with an average particle size ≤200 nm.
[0020] Mechanism of action: The carbonaceous filler, in the form of micro- and nano-sized particles, is uniformly dispersed between coal powder particles, filling the gaps between submicron to micron-sized particles. During carbonization, these high-purity carbonaceous particles fuse with the main carbon skeleton through a boron cross-linking network, further eliminating residual porosity and pushing the bulk density to an extreme level of over 550 g / L. Simultaneously, the carbonaceous filler itself can also be partially activated during the activation process, forming micropores without negatively impacting the iodine value.
[0021] The four components mentioned above form a complementary closed loop in function, and none can be omitted. Without phosphorus compounds, carbon microcrystals cannot achieve ordering, and the intrinsic density of the framework cannot be significantly improved; without boron compounds, effective chemical cross-linking cannot be formed between carbon particles, resulting in high interparticle porosity and insufficient product strength; without nitrogen-containing organic compounds, the iodine value compensation mechanism is missing, and the iodine value will significantly decrease after framework densification; without carbonaceous fillers, the gaps between micro- and nano-scale particles cannot be eliminated, and the bulk density cannot exceed 550 g / L. Only through quaternary synergy can a complete and efficient densification technology chain be formed, producing a synergistic effect greater than the sum of its parts (1+1+1+1>4).
[0022] An additive for producing flaked activated carbon from long-flame coal is described, specifically for the preparation of long-flame coal-based briquetted activated carbon. The specific steps are as follows:
[0023] Step 1: Dry each additive component at 80~90℃ to constant weight. Using long-flame coal as the single raw material, crush and grind the long-flame coal to 200~325 mesh. Weigh each component according to the proportion, add 2%~8% of the additive by mass of coal powder, and mix evenly in a high-speed mixer to ensure that the additive is evenly distributed in the coal powder.
[0024] Step 2: Feed the mixture obtained in Step 1 into a high-pressure briquetting machine and press it directly into shape under a pressure of 20~30 MPa. After crushing and screening, uniform granules of 1~3 mm are obtained.
[0025] Step 3: The granular material is carbonized in a three-stage temperature-controlled manner under an inert atmosphere (such as nitrogen):
[0026] First stage (low-temperature pre-carbonization): Increase the temperature to 300-350℃ at a rate of 3-10℃ / min and hold for 30-60 min; this stage mainly involves removing moisture and adsorbed gases, and phosphorus compounds begin to decompose and be released. and Micropores begin to form within the carbon framework; nitrogen-containing organic compounds begin to melt and partially decompose.
[0027] The second stage (medium-temperature main carbonization): The temperature is increased from the first stage to 450-500℃ at a rate of 3-8℃ / min, and held for 20-40 minutes. This stage is the main phase of vigorous pyrolysis of pulverized coal, with a large amount of volatiles released. Boron compounds are dehydrated and generated within this temperature range. It undergoes a cross-linking reaction with oxygen-containing functional groups on the carbon surface to form Network; phosphorus compounds further decompose, and phosphorus elements are embedded in the carbon skeleton to form Bond; nitrogen-containing organic compounds continuously decompose to release nitrogen-containing gases for vapor phase etching.
[0028] The third stage (high-temperature deep carbonization): The temperature is increased from the second stage to 550-650℃ at a rate of 2-5℃ / min, and held for 0.5-2 hours; this stage uses a slow heating rate to ensure… Crosslinked networks and The bonded structure is fully developed in the carbon skeleton; the nitrogen-containing organic compounds are completely pyrolyzed, and nitrogen is fully doped into the carbon skeleton to form nitrogen-containing active sites; the carbonaceous filler and the coal powder main carbon skeleton achieve good interfacial bonding at high temperature.
[0029] After carbonization, the material is naturally cooled to room temperature under an inert atmosphere to obtain carbonized material.
[0030] Step 4: Pulse-type steam activation: The carbonized material is pulse-type activated at 850~950℃ using steam as the activation medium.
[0031] During the pulse phase, steam is continuously introduced into the activation furnace for 10-20 minutes. During this phase, the steam reacts with carbon in a gasification reaction. ), to carry out deep pore expansion and pore creation, and develop microporous structures.
[0032] Stop introducing steam for 5-10 minutes during the intermittent period. During this stage, the gasification products already generated ( , The carbon (such as carbon vapor) diffuses and escapes fully from the pores, exposing fresh carbon surfaces and providing active sites for the next pulse reaction, while avoiding excessive etching and secondary loosening of the skeleton caused by water vapor remaining in the pores for a long time.
[0033] The activation process is carried out in an alternating cycle of pulse and intermittent periods, with a total activation time of 3-6 hours. After activation, the activated carbon is cooled under an inert atmosphere and then sieved to obtain tableted activated carbon.
[0034] In step four, during the pulse period, the mass ratio of water vapor to carbonized material is 0.5:1 to 3:1.
[0035] The iodine adsorption value of the prepared briquetted activated carbon is ≥1000 mg / g, and the bulk density is ≥550 g / L.
[0036] Compared with the prior art, the specific beneficial effects of this invention are reflected in:
[0037] 1. High bulk density: This invention uses long-flame coal as a single raw material, and the bulk density of the product can be stably reached above 550 g / L, which is at the same highest level as the coal blending process that relies on expensive and highly caking coal, but the raw material cost is greatly reduced and the supply chain is significantly simplified.
[0038] II. Iodine adsorption value is maintained without loss: The iodine adsorption value of the present invention is maintained above 1000 mg / g, and high packing density and high adsorption are taken into account, breaking the technical prejudice in the field that "high density inevitably sacrifices iodine value".
[0039] III. Green and Environmentally Friendly Process: This invention does not use coal tar pitch or strong alkaline compounds at all, eliminating the emission of toxic fumes (such as polycyclic aromatic hydrocarbons) and equipment corrosion from the source. The production process is clean and safe, which is in line with the development direction of green chemical industry.
[0040] IV. Significantly Improved Overall Yield: The pulsed activation of this invention effectively reduces excessive ablation through an intermittent diffusion mechanism, increasing the overall product yield from approximately 28% in the traditional long-flame coal process to over 36%, an increase of about 30%, resulting in significant economic benefits.
[0041] V. The synergistic effect is unpredictable: Comparative Examples 2-5 fully demonstrate the necessity and irreplaceability of the quaternary synergy by eliminating individual components one by one; individual or partial components cannot simultaneously achieve the dual objectives of bulk density ≥550 g / L and iodine value ≥1000 mg / g, proving that the synergistic effect is not a simple superposition of the functions of each component, but rather produces an synergistic effect of 1+1+1+1>4.
[0042] VI. Strong Technological Innovation: This invention forms a complete technical solution integrating "additive formulation - carbonization process - activation process". The temperature windows of the three-stage carbonization are precisely matched with the thermal reaction behavior of each component of the additive. Pulse activation further protects the densified skeleton. The synergy of the three processes produces the best effect. Detailed Implementation
[0043] To make the technical problems, solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments and comparative examples. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0044] Test method description:
[0045] 1. Iodine adsorption value: according to Measurement.
[0046] 2. Bulk density: based on Measurement.
[0047] 3. Overall Yield: Mass of finished activated carbon Raw coal powder quality .
[0048] 4. X-ray diffraction (XRD): employing... Radiation source, scanning range It is used to analyze the degree of ordering of carbon microcrystals.
[0049] 5. X-ray photoelectron spectroscopy (XPS): using monochromatic... X-rays were used as the excitation source to analyze the chemical state of surface elements.
[0050] Example 1
[0051] Additive preparation: Weigh out ammonium dihydrogen phosphate, boric acid, melamine, and pyrolytic carbon black (average particle size 150 nm), dry them at 80℃ to constant weight, grind them to 325 mesh, and put them into a high-speed mixer at a mass ratio of 8:15:12:65. Stir at room temperature for 30 min until uniform to obtain composite additive.
[0052] Mixing and briquetting: Using long-flame coal (32% volatile matter, 0% caking index) as the single raw material, grind it to 325 mesh, take 1000 g of coal powder, add 60 g of composite additive (accounting for 6% of the coal powder mass), and mix for 15 min. Press the mixture into briquettes under a pressure of 25 MPa, and crush and screen to obtain 1-3 mm particles.
[0053] Three-stage carbonization: Under nitrogen atmosphere, the temperature is increased to 300℃ at 5℃ / min and held for 50 min; then increased to 480℃ at 5℃ / min and held for 30 min; finally increased to 600℃ at 3℃ / min and held for 1.5 h; and then cooled to room temperature under nitrogen protection.
[0054] Pulse activation: Pulse steam activation is carried out at 900℃, with steam flowing for 12 min during the pulse period (steam to carbonized material mass ratio 0.8:1), and pausing for 8 min during the intermittent period. The process is repeated, with a total activation time of 4.5 h. The material is then cooled under an inert atmosphere and sieved.
[0055] The product performance of this embodiment is shown in Table 1.
[0056] Example 2
[0057] The additive mass ratio was changed to 5:10:8:77 (ammonium dihydrogen phosphate: boric acid: melamine: pyrolytic carbon black), and the final carbonization temperature was adjusted to 620℃. The rest was the same as in Example 1.
[0058] The product performance of this embodiment is shown in Table 1.
[0059] Example 3
[0060] The additive components were replaced with ammonium phosphate, ammonium borate, urea, and coal-based ultrafine powder. The mass ratio was 10:18:15:57, the amount of additive added was 4% of the mass of coal powder, the activation temperature was 880℃, and the rest was the same as in Example 1.
[0061] The product performance of this embodiment is shown in Table 1.
[0062] Comparative Example 1 (Blank Control: Long-flame coal, single coal type, no additives, traditional process)
[0063] Without any additives, it undergoes a single-stage carbonization process (5℃ / min to 550℃ and holding for 1 h) followed by traditional continuous steam activation (900℃, 3 h).
[0064] The product performance of this embodiment is shown in Table 1.
[0065] Comparative Example 2 (Phosphorus-free compound)
[0066] Ammonium dihydrogen phosphate was removed from the additive, and the remaining components were adjusted by mass ratio to boric acid: melamine: pyrolytic carbon black = 15:12:73. The amount of additive added was 6% of the mass of coal powder, and the rest was the same as in Example 1.
[0067] The product performance of this embodiment is shown in Table 1.
[0068] Comparative Example 3 (Boron-free compound)
[0069] Boric acid was removed from the additive, and the remaining components were adjusted by mass ratio to ammonium dihydrogen phosphate: melamine: pyrolytic carbon black = 8:12:80. The amount of additive added was 6% of the mass of coal powder, and the rest was the same as in Example 1.
[0070] The product performance of this embodiment is shown in Table 1.
[0071] Comparative Example 4 (without nitrogen-containing organic compounds)
[0072] Melamine was removed from the additive, and the remaining components were adjusted by mass ratio to ammonium dihydrogen phosphate:boric acid:pyrolytic carbon black = 8:15:77. The amount of additive added was 6% of the mass of coal powder, and the rest was the same as in Example 1.
[0073] The product performance of this embodiment is shown in Table 1.
[0074] Comparative Example 5 (without carbonaceous filler)
[0075] The pyrolytic carbon black was removed from the additive, and the remaining components were adjusted by mass ratio to ammonium dihydrogen phosphate:boric acid:melamine = 8:15:12. The amount of additive added was 2.1% of the coal powder mass (to make the total amount of active components added equivalent to that in Example 1), and the rest was the same as in Example 1.
[0076] The product performance of this embodiment is shown in Table 1.
[0077] Comparative Example 6 (using only long-flame coal, pitch, and strong alkali, without blending with other coal, based on existing technology and processes)
[0078] To objectively compare the effects of using the pitch + strong alkali route under single long-flame coal conditions, this comparative example uses long-flame coal as the single coal type (without adding any other coal types), and adds 4.5% high-temperature modified coal pitch and 0.5% KOH by mass ratio. After mixing, the mixture is briquetteed, carbonized in one stage (5℃ / min to 550℃ and held for 1 h), and activated with continuous steam at 900℃ for 3 h.
[0079] The product performance of this embodiment is shown in Table 1.
[0080] Table 1 Product performance of each embodiment and comparative example
[0081]
[0082] Table 2 Comparison of XRD microcrystalline parameters (Example 1 and Comparative Example 1)
[0083]
[0084] As shown in Table 2, the 002 diffraction peak of Example 1 shifted significantly to a higher angle, the interlayer spacing decreased, and the microcrystal stacking height increased, indicating that the phosphorus compound successfully induced the ordered arrangement of carbon microcrystals and significantly improved the compactness of the carbon skeleton.
[0085] Table 3 Product of Example 1 analyze
[0086]
[0087] Table 3 confirms that nitrogen-containing organic compounds successfully incorporated highly reactive pyridine nitrogen and pyrrole nitrogen into the carbon skeleton, which together account for 73.8%, providing direct chemical evidence that the iodine value can remain high.
[0088] Results analysis:
[0089] (1) Verification of the effects of Examples 1-3: Using the additives and processes of the present invention, with long-flame coal as the single raw material, the bulk density of all samples was higher than 550 g / L (up to 589 g / L), the iodine value was ≥1000 mg / g (up to 1082 mg / g), and the total yield exceeded 35% (up to 37.1%), fully achieving the technical objectives of the present invention. Example 3 used different combinations of ammonium phosphate, ammonium borate, urea, and coal-based ultrafine powder, which also achieved good results, proving that the additive formulation of the present invention has a wide range of component selection.
[0090] (2) Blank control of Comparative Example 1: Without the use of any additives and the step-by-step carbonization and pulse activation process of the present invention, the bulk density of single long-flame coal using conventional processes is only about 350 g / L. This fully illustrates the inherent limitations of long-flame coal and also confirms the necessity of the present invention.
[0091] (3) Validation of quaternary synergy in Comparative Examples 2-5: By eliminating individual components one by one, the irreplaceable nature of quaternary synergy was revealed:
[0092] Phosphorus-free (Comparative Example 2): density was only 468 g / L, proving that phosphorus-induced microcrystalline ordering is crucial for densification;
[0093] Boron-free (Comparative Example 3): with a density of only 495 g / L and poor strength, proving that the cross-linked network constructed by boron is the guarantee of the integrity of the skeleton;
[0094] No nitrogen-containing compounds (Comparative Example 4): Although the density reached 545 g / L, the iodine value did not reach 1000 mg / g, proving that the iodine value compensation mechanism of nitrogen-containing compounds is indispensable;
[0095] Carbon-free filler (Comparative Example 5): density of only 512 g / L, demonstrating that physical interstitial filling makes a key contribution to exceeding the density threshold of 550 g / L.
[0096] The above results fully demonstrate that all four elements must be present to simultaneously meet the requirements of high packing density and high iodine value. This synergistic effect is unexpected by those skilled in the art.
[0097] (4) Comparative Example 6 (Comparison with Existing Technology): Under the condition of single long-flame coal, adding only pitch and strong alkali without adding other coal types cannot achieve the "double high" indicators of bulk density ≥550 g / L and iodine value ≥1000 mg / g (the actual bulk density is only 473 g / L and the iodine value is only 989 mg / g). This fully demonstrates that the reason why the existing technical solution can achieve high bulk density is that the core lies in the coal blending system of non-caking coal and strongly caking coal, rather than pitch and strong alkali themselves. When the basic coal type is not available (such as single long-flame coal), the solution fails. The technical route of this invention, which reconstructs the carbon skeleton at the molecular level through chemical additives, precisely solves this technical problem. The two technical solutions are fundamentally different in terms of applicable objects and technical mechanisms.
[0098] (5) The XRD data in Tables 2 and 3 confirm the structural basis of phosphorus-induced microcrystal ordering, and the XPS data confirm the chemical evidence of nitrogen-doped active sites.
[0099] A major breakthrough for single long-flame coal: This invention discloses for the first time a composite additive and supporting process that enables long-flame coal to be used as a single coal type, without relying on any other coal type blending, asphalt and strong alkali, to prepare briquetted activated carbon with a bulk density ≥550g / L and an iodine value ≥1000mg / g.
[0100] The invention pioneered a four-component synergistic densification mechanism: It proposes for the first time a four-fold synergistic mechanism of "phosphorus-induced microcrystalline ordering + boron-constructed cross-linking network + nitrogen-containing compound iodine value compensation + carbonaceous filler physical interstitial filling," and designs a dedicated additive based on this mechanism. Comparative Examples 2-5, by systematically eliminating individual components, fully demonstrate that all four components are indispensable, and that no single or partial mechanism can achieve the "dual-high" target.
[0101] The essential differences and significant advancements compared to the closest existing technologies:
[0102] The technical approaches are different: the core technology of the existing process lies in using the complementary properties of different coal types (non-caking coal + strongly caking coal) to balance density and adsorption, which belongs to the physical coal blending route; the present invention modifies the carbon skeleton of long-flame coal at the molecular level (microcrystalline ordering, chemical cross-linking, nitrogen doping) through chemical additives, which belongs to the chemical modification route. The technical principles of the two are completely different.
[0103] Different types of coal are applicable: Existing technologies are not applicable to a single long-flame coal system (Comparative Example 6 proves its failure); This invention precisely solves the technical problem of long-flame coal, which is the most difficult coal to densify.
[0104] The environmental friendliness and economic efficiency differ: This invention does not use asphalt and strong alkali, eliminating toxic fumes and equipment corrosion at the source, resulting in a higher total yield (37% vs. approximately 30%), and thus superior environmental performance and economic benefits.
[0105] Technological advancements: This invention achieves a bulk density of over 580 g / L for long-flame coal activated carbon without the need for high-quality coal blending, which is comparable to or even better than the highest level of coal blending technology, representing a significant advancement.
[0106] Synergistic innovation in the process: The temperature window of the three-stage stepped temperature-controlled carbonization process is precisely matched to the thermal reaction characteristics of each additive component (decomposition of phosphorus, cross-linking of boron, and doping of nitrogen). The pulsed activation process protects the densified framework through an intermittent diffusion mechanism, reducing excessive ablation. There is a close compatibility between the additives and the process, forming an inseparable overall technical solution.
[0107] Unexpected technical effects: This invention overcomes the dual technical biases of "high iodine value activated carbon inevitably has low bulk density" and "long-flame coal must be blended to achieve high density", and realizes the production of high-end activated carbon products with performance comparable to or even surpassing that of high-quality coal blending processes using the lowest grade and cheapest coal type without the use of any harmful additives.
[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the scope of the present invention.
Claims
1. An additive for producing flamed activated carbon from long-flame coal, characterized in that, By mass percentage, it consists of the following components: 5%~10% phosphorus compounds, 10%~20% boron compounds, 5%~15% nitrogen-containing organic compounds, and 55%~80% carbonaceous filler.
2. The additive for producing flaked activated carbon from long-flame coal according to claim 1, characterized in that, The phosphorus compound is one or any combination of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate.
3. The additive for producing flaked activated carbon from long-flame coal according to claim 2, characterized in that, The boron compound is one or any combination of boric acid, ammonium borate, and borax.
4. The additive for producing flaked activated carbon from long-flame coal according to claim 3, characterized in that, The nitrogen-containing organic compound is one or any combination of melamine, urea, and caprolactam.
5. The additive for producing flamed activated carbon from long-flame coal according to claim 4, characterized in that, The carbonaceous filler is one or any combination of nano-carbon black, carbon nanotubes, pyrolytic carbon black, and coal-based ultrafine powder.
6. The application of the additive for producing flaked activated carbon from long-flame coal as described in any one of claims 1-5, characterized in that, The specific steps for preparing long-flame coal-based briquetted activated carbon are as follows: Step 1: Dry each additive component at 80~90℃ to constant weight, crush and grind the long-flame coal to 200~325 mesh, add 2%~8% of the additive by weight of coal powder, and mix evenly; Step 2: Press the material into blocks under a pressure of 20~30 MPa, then crush and screen to obtain 1~3 mm granules; Step 3: Conduct three-stage temperature-controlled carbonization under an inert atmosphere: The first stage involves raising the temperature to 300-350℃ at a rate of 3-10℃ / min and holding it for 30-60 min. The second stage involves increasing the temperature to 450-500℃ at a rate of 3-8℃ / min and holding the temperature for 20-40 min. The third stage involves increasing the temperature to 550-650℃ at a rate of 2-5℃ / min and holding it at that temperature for 0.5-2 hours. After carbonization, the material is naturally cooled to room temperature under an inert atmosphere to obtain the carbonized material. Step 4: Pulse activation of the carbonized material at 850~950℃ using steam as the activation medium: During the pulse period, steam is introduced into the activation furnace for 10~20 min, and during the intermittent period, the steam is stopped for 5~10 min. The pulse and intermittent periods are alternated, with a total activation time of 3~6 h. After activation, the material is cooled under an inert atmosphere and sieved to obtain the pressed activated carbon.
7. The application of the additive for producing flaked activated carbon from long-flame coal according to claim 6, characterized in that, In step four, during the pulse period, the mass ratio of water vapor to carbonized material is 0.5:1 to 3:
1.
8. The application of the additive for producing flamed activated carbon from long-flame coal according to claim 6, characterized in that, The iodine adsorption value of the prepared briquetted activated carbon is ≥1000 mg / g, and the bulk density is ≥550 g / L.
Citation Information
Patent Citations
A method for preparing coal-based briquetted activated carbon with high adsorption capacity and high bulk density
CN106044766B
